.W.L تأثیر استخدام استراتیجیة . في التحصیل المعرفي و أداء بعض المھارات الدفاعیة بكرة السلة لطلبة الصف الثاني - عماد طعمة راضي (الرياضة المعاصرة)
Chapter provided to ensure the first- and the importance of research of the most important of these materials is material basketball both theoretical and practical as it is for students to the field of micro- work (which is practical education ) before graduation and then the real work in the field after graduation . It is found on the principles of strategy KWL show the researcher they represent the contribution is serious about making the student the center of the educational process and its goal and purpose are based on the higher-order thinking and thus provide a solution to get rid of the negative role played by the student to the role of master student to the stage of decision-making and mastering the information and skills of a game such as football Basketball , here lies the importance of research as a new attempt and the addition of quality in teaching and learning in the field of physical education and basketball in particular , it is a transfer of the experiences of learning strategies to talk in the fields of education science the other to the sports field to be applied in the field of practical learning defensive skills and cognitive achievement basketball . The research problem or failure lies in modern teaching strategies attention by teachers as well as there are questions of a general weakness of student achievement scores for material basketball ( theoretical practical ) . Included as well as the goals of research aims to: -Understand the impact of the use of KWL strategy in the collection of knowledge and performance skills of basketball. The research hypotheses are -There are significant differences between the results of the tests and the results of tests tribal dimensional in the collection of knowledge and skills for the defense of the experimental group and the control group -There are significant differences between the results of the post tests to collect the knowledge and skills of defense between the experimental group and Aldhabto and in favor of the experimental group. This included the areas of research and the field of human temporal and spatial domain